2007
DOI: 10.1097/sla.0b013e31811f3fb7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Lymph Node Metastasis in Early Gastric Cancer With Submucosal Invasion

Abstract: Lymphatic involvement and tumor size are independent risk factors for a lymph node metastasis in early gastric cancer with submucosal invasion. Minimal invasive treatment, such as endoscopic mucosal resection, may be possible in highly selective submucosal cancers with no lymphatic involvement, SM1 invasion, and tumor size <1 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(115 citation statements)
references
References 16 publications
6
101
0
6
Order By: Relevance
“…An et al (2007) reported that no lymph node metastasis was observed in the cases with no lymphatic involvement, SM1 invasion, and tumor size <1cm. The study in a large group of Japanese patients found that in cases where the histology is a differentiated type and without vascular invasion, the rate of lymph node metastasis in submucosal invasion less than 500μm was only 0.9% (Ishikawa et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al (2007) reported that no lymph node metastasis was observed in the cases with no lymphatic involvement, SM1 invasion, and tumor size <1cm. The study in a large group of Japanese patients found that in cases where the histology is a differentiated type and without vascular invasion, the rate of lymph node metastasis in submucosal invasion less than 500μm was only 0.9% (Ishikawa et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Yamao et al ( Yamao et al, 1996) reported that lymphatic invasion, histological ulceration of tumors and larger tumor sizes are independent risk factors for lymph node metastases in intramucosal early gastric cancer. An et al (2007) reported that tumor size and lymphatic involvement were independent risk factors for lymph node metastasis in early gastric cancer with submucosal invasion. Shen et al (2009) reported that histological classification, macroscopic type, tumor size, depth of gastric carcinoma infiltration, and the presence of vascular or lymphatic invasion were significantly and independently related to lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is still impossible, however, to accurately detect cancer-positive lymph nodes by imaging techniques such as endoscopic ultrasound (EUS) or computed tomography (CT) [15,16]. For this reason, multiple patient-and tumor-related variables are investigated as predictors of lymph node involvement, especially in EGC with invasion of the submucosa [17].…”
mentioning
confidence: 99%
“…However, there are cases in which lymph node metastasis is not associated with ly and vice versa. The correlation between ly and lymph node metastasis has been shown in gastric (11) and colorectal cancer (12). This correlation is a general relationship irrespective of the depth of invasion (3).…”
Section: Discussionmentioning
confidence: 98%